Liposomal Irinotecan Accumulates in Metastatic Lesions, Crosses the Blood-Tumor Barrier (BTB), and Prolongs Survival in an Experimental Model of Brain Metastases of Triple Negative Breast Cancer - Mohammad, Afroz S. (Pharm Res, 2018)
PURPOSE: The blood-tumor barrier (BTB) limits irinotecan distribution in tumors of the central nervous system. However, given that the BTB has increased passive permeability we hypothesize that liposomal irinotecan would improve local exposure of irinotecan and its active metabolite SN-38 in brain metastases relative to conventional irinotecan due to enhanced-permeation and retention (EPR) effect. METHODS: Female nude mice were intracardially or intracranially implanted with human brain seeking breast cancer cells (brain metastases of breast cancer model). Mice were administered vehicle, non-liposomal irinotecan (50 mg/kg), liposomal irinotecan (10 mg/kg and 50 mg/kg) intravenously starting on day 21. Drug accumulation, tumor burden, and survival were evaluated. RESULTS: Liposomal irinotecan showed prolonged plasma drug exposure with mean residence time (MRT) of 17.7 ± 3.8 h for SN-38, whereas MRT was 3.67 ± 1.2 for non-liposomal irinotecan. Further, liposomal irinotecan accumulated in metastatic lesions and demonstrated prolonged exposure of SN-38 compared to non-liposomal irinotecan. Liposomal irinotecan achieved AUC values of 6883 ± 4149 ng-h/g for SN-38, whereas non-liposomal irinotecan showed significantly lower AUC values of 982 ± 256 ng-h/g for SN-38. Median survival for liposomal irinotecan was 50 days, increased from 37 days (p<0.05) for vehicle. CONCLUSIONS: Liposomal irinotecan accumulates in brain metastases, acts as depot for sustained release of irinotecan and SN-38, which results in prolonged survival in preclinical model of breast cancer brain metastasis.